2010
DOI: 10.1007/s00595-009-4158-7
|View full text |Cite
|
Sign up to set email alerts
|

Rectal obstruction by a giant pharmacobezoar composed of magnesium oxide: Report of a case

Abstract: This report presents the rare case of a 75-year-old woman who developed a rectal obstruction caused by a pharmacobezoar, following the long-term ingestion of magnesium oxide cathartics for constipation. She was admitted to the hospital with lower abdominal pain and nausea. Abdominal computed tomography and magnetic resonance imaging showed that a huge calcified mass caused the rectal obstruction. A divided sigmoid colostomy was performed to relieve her symptoms, a colonoscopy from the distal stoma delineated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although several bezoar case series have been reported from Western countries (3)(4)(5)(6) and South Korea (7), only single case reports or small case series describing a few Japanese patients are available, to our knowledge (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In Japan, the epidemiology and etiology of bezoars have not been fully elucidated, and treatment is empirical.…”
Section: Introductionmentioning
confidence: 99%
“…Although several bezoar case series have been reported from Western countries (3)(4)(5)(6) and South Korea (7), only single case reports or small case series describing a few Japanese patients are available, to our knowledge (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In Japan, the epidemiology and etiology of bezoars have not been fully elucidated, and treatment is empirical.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectroscopy and chemical analyses revealed that the mass's major component was magnesium oxide. Shigekawa et al reported another case of a 75-year-old woman who presented with lower abdominal pain and nausea ( 16 ). The patient had been taking magnesium oxide cathartics for 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…A chemical analysis of the bezoar showed that its major component was magnesium oxide. Previous reports have described patients with magnesium oxide bezoars in the small intestine ( 15 ) and rectum ( 16 ). These bezoars might have been formed in the stomach and migrated into the intestine.…”
Section: Discussionmentioning
confidence: 99%